Evaluation of life quality of epileptic patients depending on selected clinical and demographic factors - Nowak, Elżbieta (Polish Journal of Public Health, 2009)
Introduction. The assessment of quality of life has significance in case of neurological diseases, which often are protracted, causing a reduction of physical and mental functioning, worsening the functioning of an ill person in society. Epilepsy is a special disease with certain characteristics, which differs from many other chronic diseases. Basic effects occur irregularly, unpredictably, disturbing all areas of functioning. In the opinion of the patient, most harsh and handicapping is a sense of loss of control and full dependence on the disease. In case of rare attacks the anxiety against the unexpected occurrence of the attack is one of the major factors limiting the activity of patients. This feeling significantly impedes normal activities, causing a sense of depending on others and often preventing to continue work. Repeated attacks disturb lifestyle and are one of the major causes of ill-functioning of patients below their capabilities and expectations.Aim. The aim of this work was to assess rating relationship between quality of life of patients with epilepsy and selected demographic parameters and the parameters which set out the clinical status of patients depending on the degree of social functioning.Results. All patients were treated ambulatorily in Provincial Specialist Neuropsychiatric Health Care Centre. The tests were performed on 244 patients with epilepsy, including 114 women (53%) and 130 men (47%), aged from 19 to 65. In the tested group of patients, as well as in other studies conducted in our country, the quality of life was clearly reduced – 44.39. The quality of life of patients with epilepsy is affected by both demographic factors, as well as some of the factors determining the clinical status. Demographic factors, which, above all, in negatively affect the quality of life of patients with epilepsy are older age and restrictions in social life. The factors determining the status of the most important clinical significance for the quality of life is the type of seizures and the occurrence of side effects. In the analysed material up to 57% of respondents claimed that the attacks severely limited their activity and social life. The anxiety (77%) that the attack occurs in a public place is one of the major factors worsening the quality of life of patients with epilepsy.